Games for developing understanding and differentiation of grammatical forms accidence of children with mental development delay - Kiryuhina D. P. (Education and science in the modern context, 2016)
In article it is told about importance of formation of a grammatical system of the speech of children with the detained mental development. The complex of games on a problem of formation of a grammatical system of the speech of children with the detained mental development is considered.
Keywords: игра; задержка психического развития; грамматический строй речи; словообразование; game; грамматическая форма; delay of mental development; grammatical system of the speech; grammatical form; word formation